Efeitos cardiovasculares da sinvastatina em monoterapia e associada ao enalapril, em ratos espontaneamente hipertensos - Bortolini, Márcia Rejane Sordi (2018)
Theoretical Background: Cardiovascular disease is the leading cause of death in developed countries and it is an important cause of morbidity, dependency and high health costs. Furthermore, hypertension has a high prevalence in the various communities and it is a major risk factor for cardiovascular disease, kidney disease and cognitive impairment. Thus, it is clear that the modification of cardiovascular risk factors reduces cardiovascular and renal morbidity and mortality. Objective: This study evaluated the effects of simvastatin associated with enalapril in blood pressure and transversal diameter of cardiomyocytes in spontaneously hypertensive rats. Materials and methods: We used spontaneously hypertensive male rats, adults, subject to the same environmental conditions, divided into four groups (control, simvastatin, enalapril and combination of simvastatin and enalapril). The experiment lasted four weeks. Earlier, the body weight, the heart rate and the sistemic blood pressure by tail plethysmography were registered. At the end of experiment, the body weight, the heart and the left ventricle weight were measured. In addition, the heart rate and the systolic blood pressure were registered by plethysmography and the transversal diameters of cardiomyocytes were measured. The statistical treatment of results was done analyzing the results by a completely randomized design in a factorial and in a split plot and UNIANOVA. Results: There was a reduction in heart rate in the simvastatin group when compared to the control group. Systolic blood pressure in the enalapril groups was also reduced, both in monotherapy and in the association of this with simvastatin. The weight of the animals in the enalapril group was also lower than those of the control group. No change was observed in the weight of the heart and left ventricle in any of the treated groups. There was an increase in the transverse diameter of the cardiomyocytes in the simvastatin and enalapril groups and no change when the two drugs were associated, in relation to the control group. Conclusions: Simvastatin monotherapy promotes a reduction in heart rate. Enalapril alone does not alter heart rate. Enalapril and simvastatin, when given alone, increase the cross-sectional diameter of cardiomyocytes and this effect is abolished by combination therapy. In combination with enalapril, simvastatin potentiates the reduction of systolic blood pressure in SHR. There is interruption of weight gain with enalapril monotherapy, which is suppressed when simvastatin is associated with treatment.